Analytical model of hybrid MMC for dynamic and steady‐state studies. Issue 13 (12th December 2017) - Lu, Xiaojun; Xiang, Wang; Lin, Weixing; Wen, Jinyu
Abstract : This study researched the analytical models for the modular multilevel converter (MMC) with its arm mixed with half‐bridge submodules and full‐bridge submodules, named as hybrid MMC. The state‐space model and steady‐state model of hybrid MMC under rotating frame are proposed. The phasor modelling method is employed to describe the internal dynamics of the converter. Modulation signals combined with the elementary control of hybrid MMC are considered in the modelling. The accuracy of the analytical models is verified by extensive time‐domain simulation in contrast with PSCAD/EMTDC models. A 'select and check' method is proposed to determine the feasible operating zone of hybrid MMC considering multiple operating constraints. The operating zones of the test hybrid MMC under different DC voltage levels are analysed.